Securing Gateways within Clustered Power Centric Network of Nodes - Qaisar Javaid; Muhammad Daud Awan; Syed Hasnain A. Naqvi (Mehran University Research Journal of Engineering and Technology, 2016)
Knowledge Networks are gaining momentum within cyber world. Knowledge leads to innovation and for this reason organizations focus on research and information gathering in order to gain and improve existing knowledge. This of information era, which is primarily based on world wide web technologies, enables significantly expanded networks of people to communicate and collaborate 'virtually' across teams, across entire organizations and across the world, anytime and anywhere. Innovations in computing and telecommunications have transformed the corporations from structured and manageable types to interwoven network of blurred boundaries such as; ad hoc networks and mobile wireless networks, etc. This study explores knowledge networks in Information Technology and security leaks that are found, as well as measures that are taken to counter this menace which is coming up with optimal Secure Clustered Power Centric node network. The paper concludes these measures, evaluating and integrating them to come up with a secured network design.